Non Iatrogenic acute meningeal inflammation after laminectomy in rats (Veterinary Science, 2017)
The laminectomy in rats is a procedure commonly used in bothfunctionality experimental designs and in electrophysiology assays.Also, rats had been used as an experimental model of traumaticand compressive lesions of the spinal cord. Laminectomies were performed in healthy rats anaesthetized and the degree of medullary inflammatory response was quantified after laminectomy and compared to non-operated rats which were anaesthetized and fixed in the same way. The acute meningeal inflammatory response in spinal segments exposed and those located cranially and caudally to the laminectomy was observed
Keywords: laminectomy; aseptic meningitis; rat